The Outcome of Rectal Cancer Patients During SARS-CoV-2 Pandemic - Florin BOBIRCA; Dan DUMITRESCU; Lidia BELEGA; Anca BOBIRCA; Traian PATRASCU (Modern Medicine)
Introduction: Rectal cancer is a complex pathology that requires a multidisciplinary approach according to current guidelines, and surgery is one of the main stages of treatment, the type of intervention being established in relation to the location of the tumor at the rectal level. Material and method: The present study aims to analyze the diagnostic features, study the evolution, treatment and complications of patients with rectal cancer in a period marked by the SARS-CoV-2 pandemic. After completing the inclusion criteria, but also the exclusion group, the remaining group consisted of 55 patients with rectal cancer. Results: For the 55 patients, abdominal-pelvic rectal amputation was performed in 17 cases, rectosigmoid resection with colostomy in 13 cases, and rectosigmoid resection with anastomosis in 25 cases. It was also taken into account that the access to medical services was delayed compared to the pre-pandemic period, the increase of the time interval between the treatment stages being an important aspect of the study. Complications associated with surgery have been reported in 13 patients, the most common being the pelvic abscess. Conclusions: The results of the study show a high incidence rate in the age group 60-69 years, with a predominance of males, a delay in making the diagnosis of certainty, an extension of the period from the beginning of neoadjuvant treatment to access to surgery, and the rate of postoperative complications is similar to that described in other studies conducted during the SARS-CoV-2 pandemic, but also outside it.